Storm prey - Sandford, John (New York G.P. Putnam's Sons, 2016)
Witnessing a robbery gone wrong that has caused the death of a pharmacy employee, Lucas Davenport's surgeon wife, Weather Karkinnen, is targeted by the thieves when they become fearful that she can identify them
1
Keywords: Murder -- Investigation -- Minnesota -- Minneapolis -- Fiction; Witnesses -- Minnesota -- Minneapolis -- Fiction